2021
DOI: 10.5603/cj.a2019.0031
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery height differences and their effect on fractional flow reserve

Abstract: Background: Fractional flow reserve (FFR) uses pressure-based measurements to assess the severity of a coronary stenosis. Distal pressure (Pd) is often at a different vertical height to that of the proximal pressure (Pa). The difference in pressure between Pd and Pa due to hydrostatic pressure, may impact FFR calculation. Methods: One hundred computed tomography coronary angiographies were used to measure height differences between the coronary ostia and points in the coronary tree. Mean heights were used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…According to Pascal´s law the hydrostatic pressure in the coronary arteries can be assumed as 0.77 mmHg per cm height difference, in case of a normal mass density (1050 kg/ m 3 ). Studies applying CT coronary angiography have previously showed that pressure differences are systematically detectable between the anterior and posterior coronary territories in supine position [15][16][17][18]. Moreover, height measurements at the highest or lowest points of the individual vessels indicated remarkable differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Pascal´s law the hydrostatic pressure in the coronary arteries can be assumed as 0.77 mmHg per cm height difference, in case of a normal mass density (1050 kg/ m 3 ). Studies applying CT coronary angiography have previously showed that pressure differences are systematically detectable between the anterior and posterior coronary territories in supine position [15][16][17][18]. Moreover, height measurements at the highest or lowest points of the individual vessels indicated remarkable differences.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, intracoronary pressure measurements (resting Pd/Pa and FFR) were carried out in both supine and prone positions, and height differences were analyzed based on CT images [15]. These studies unequivocally found a significantly lower resting Pd/Pa and FFR values measured in the LAD, while higher values were demonstrated when measurements were carried out in the CX or RCA [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a factor is the effect of the hydrostatic pressure created by the height difference between the distal position of the pressure wire sensor and the coronary ostium where pressure equalization took place. Coronary arteries lie in different vertical planes [ 6 ] and it has been shown that there is significant height variation between the proximal and distal vessels when the patient is lying flat (such as during coronary angiography and invasive physiological measurements) [ 7 , 8 ]. In clinical practice, this hydrostatic pressure effect is ignored, as the actual pressure gradient is usually small (<5 mmHg) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, this hydrostatic pressure effect is ignored, as the actual pressure gradient is usually small (<5 mmHg) [ 9 ]. Nevertheless, recent studies have suggested that the hydrostatic pressure gradient influences significantly pressure-based physiological indices [ 7 , 10 , 11 , 12 , 13 , 14 , 15 ], and as such the quantification of the hydrostatic impact on clinical practice remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%